A Recipe for Madness: Parenthood in the Era of Covid‐19. (21st March 2021) - Elder, Laurel; Greene, Steven
Abstract : Objectives: This article seeks to understand the economic, mental health, and political impacts on American parents in the era of Covid‐19. Methods: We draw on survey data from a diverse national sample collected in September 2020 and employ multivariate analysis to explore how Covid‐19 has uniquely affected the attitudes and life experiences of American parents. Results: We find that Covid‐19 has been unusually burdensome for parents as they are more likely to have experienced negative physical and mental health outcomes and suffer more negative financial impacts. Despite the challenges parents face, they also remain cautious about in‐person school and vaccinations. Although mothers have been the focus of much news coverage, we find that both mothers and fathers have been similarly and negatively impacted by Covid‐19. Conclusion: American parents are suffering at distinctively high levels during this pandemic. In order to recover, policymakers will need to target outreach and support tailored to the needs and issues facing parents.